The invisible hand of short selling: Does short selling discipline earnings management? - MASSA, Massimo (Institutional Knowledge at Singapore Management University, 2015)
We hypothesize that short selling has a disciplining role vis-a-vis firm managers that forces them to reduce earnings management. Using firm-level short-selling data for thirty-three countries collected over a sample period from 2002 to 2009, we document a significantly negative relationship between the threat of short selling and earnings management. Tests based on instrumental variable and exogenous regulatory experiments offer evidence of a causal link between short selling and earnings management. Our findings suggest that short selling functions as an external governance mechanism to discipline managers.